2006
DOI: 10.1007/s11270-006-9092-3
|View full text |Cite
|
Sign up to set email alerts
|

The Potted-Plant Microcosm Substantially Reduces Indoor Air VOC Pollution: II. Laboratory Study

Abstract: Indoor air-borne loads of volatile organic compounds (VOCs) are usually significantly higher than those outdoors, and chronic exposures can cause health problems. Our previous laboratory studies have shown that the potted-plant microcosm, induced by an initial dose, can eliminate high airborne VOC concentrations, the primary removal agents being potting-mix microorganisms, selected and maintained in the plant/root-zone microcosm. Our office field-study, reported in the preceding paper, showed that, when total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 20 publications
5
64
0
Order By: Relevance
“…Moreover, previous studies found three major channels of air-pollutant decomposition by houseplants: most air-pollutant decomposition was a result of photosynthesis by houseplants after absorbing air pollutants through the stomata (Kondo and Saji, 1992), and the remainder was adsorption by media (Orwell et al, 2006;Wood et al, 2002) or with the help of microbes in the rhizosphere (Godish and Guindon, 1989). In a 1-m 3 airtight chamber, a pot without plants caused about a 100-μg decrease in formaldehyde for 5 h but a pot of fatsia plants resulted in an approximately 700-μg decrease during the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies found three major channels of air-pollutant decomposition by houseplants: most air-pollutant decomposition was a result of photosynthesis by houseplants after absorbing air pollutants through the stomata (Kondo and Saji, 1992), and the remainder was adsorption by media (Orwell et al, 2006;Wood et al, 2002) or with the help of microbes in the rhizosphere (Godish and Guindon, 1989). In a 1-m 3 airtight chamber, a pot without plants caused about a 100-μg decrease in formaldehyde for 5 h but a pot of fatsia plants resulted in an approximately 700-μg decrease during the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Indoor plants, especially such species as English ivy and spider plant, have been shown to reduce levels of many VOCs (81,140). Bacteria in the soil may account for some VOC scavenging attributed to the plants (102).…”
Section: Air Qualitymentioning
confidence: 99%
“…Furthurmore, hydroxylation is considered to be the first step of the aromatic ring cleavage of benzene and toluene in higher plants (Ugrekhelidze, 1997). Besides, a substantial role of microorganisms in the growth medium in removing benzene and toluene was also reported by previous researches (Orwell et al, 2004;Orwell et al, 2006;Wood et al, 2002;Wood et al, 2006).…”
Section: Benzene and Toluenementioning
confidence: 83%